SAT0691 PHYSICIAN–PATIENT AGREEMENT IN A RHEUMATOLOGY CONSULTATION. (June 2019) - Rodrigues, Joana; Fonseca, Diogo; Vicente, Vera; Faria, Daniela; Neves, Joana; Silva, Joana; Azevedo, Soraia; Peixoto, Daniela; Teixeira, Filipa; Alcino, Sérgio; Afonso, Carmo; Tavares-Costa, José
Abstract : Background: Several aspects of the consultation have already been studied. These usually comprise the patient satisfaction, patient enablement, physician–patient interaction and physician–patient agreement. 1 After consultations, the physician's perceptions differed from the patient's in the illness level, cause and nature of the problem and the content of the consultation. 2 Greater physician–patient agreement on consultations was associated with higher patient global satisfaction. 3 Agreement on problems requiring follow-up was associated with a better outcome. 4 Objectives: Assessment of physician–patient agreement in Rheumatology consultation. Methods: A 10 item questionnaire - "Consultation Assessment Instrument" (CAI) - was constructed with the aim of assessing physician-patient agreement. It was anonymously applied, after the consultation, to the patient and physician. The higher the score obtained, the more positive the consultation experience. Patients above 18 years of age, with an established diagnosis of inflammatory joint disease under biological therapy were included. Items were evaluated and index of proportional agreement for the dichotomized answers - agree (Ppos ) and disagree (Pneg ) - was calculated. Results: 102 observations were obtained, corresponding to 10 physicians and 102 patients. Most patients were female (53.9%) with a mean age of 51.5 ±12.7 years old. Rheumatoid Arthritis was the most prevalent diagnosis (40.2%) and more than half of patients were in disease remission [28-joint Disease Activity Score (DAS28) <2.6 or Ankylosing Spondylitis Disease Activity Score (ASDAS PCR) <2.1]. Higher CAI scores correlated with lower Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) scores (r=-0.376; p<0.05). Also, patients with mild disease (score <3.2) by DAS28 had higher CAI scores (low disease = 37±3.8; moderate disease = 35.8±4.3; high disease = 35±2.3; p=0.039). It was also found that the more satisfied the patient, the lower the Bath Ankylosing Spondylitis Functional Index (BASFI) (r=-0.334; p<0.05) and ASDAS PCR scores [low disease = 35.3±4.2; high disease = 30.5±7.8; p=0.001]. There was no statistically significant association between CAI total score and Health Assessment Questionnaire (HAQ) score, ASDAS PCR or BASFI. Patient's satisfaction did not show an association with DAS28, HAQ or BASDAI scores.Physician-patient agreement was high in 9 of the 10 items. Highest agreement was obtained for consultation satisfaction and the lowest for explanation of treatment importance in disease control. There was no statistically significant association between physician-patient agreement and disease activity, disability scores or patient satisfaction. Conclusion: Both patient and physician tend to show a positive experience towards Rheumatology consultation. Patients with a more positive experience had lower disease activity scores. Physician–patient agreement was high in the majority of the consultation aspects. CAI could be useful as a mental checklist in daily practice or as an educational tool for training consultation skills. References: [1] GC Ahlén, et al. Physician–patient questionnaire to assess physician–patient agreement at the consultation, Family Practice. 2007:24(5):498–503.DOI.org/10.1093/fampra/cmm043 [2] Martin E, et al. Why patients consult and what happens when they do. BMJ. 1991;303(6797):289-92. [3] Fagerberg C, et al. How well do patient and general practitioner agree about the content of consultations?, Scandinavian Journal of Primary Health Care. 1999:17(3):149-152.DOI: 10.1080/028134399750002557 [4] Starfield B, et al. The influence of patient-practitioner agreement on outcome of care. Am J Public Health. 1981;71(2):127-31. Disclosure of Interests: None declared